THE LEVEL OF EOSINOPHILIC CATIONIC PROTEIN IN PATIENTS WITH ATOPIC BRONCHIAL ASTHMA IN COMBINATION WITH GASTROESOPHAGEAL REFLUX DISEASE - I. S. Razikova; F. Kh. Irsalieva; M. Yu. Abidjanova; G.I. Mardonova (American Journals Publishing, 2026)
The aim of the study was to investigate the level of eosinophil cationic protein (ECP) in the blood serum of patients with atopic bronchial asthma (ABA) and its combination with gastroesophageal reflux disease (GERD). 40 people were examined, including 10 healthy individuals (control), 12 patients with isolated A B A, and 18 patients with A B A + GERD. The ECP level was determined by ELISA. The values mean were: control - 15.6 ± 4.3 μg/L; isolated A B A - 46.2 ± 11.1 μg/L (p < 0.01); ABA + GERD - 68.9 ± 14.6 μg/L (p < 0.001). ECP correlated positively with the eosinophil count (r = 0.67) and IgE level (r = 0.54) and negatively with FEV₁ (r = –0.61). The most pronounced systemic eosinophil activation was revealed in patients with combined pathology. The obtained data confirm the diagnostic and prognostic value of determining ECP as a marker of systemic inflammation and therapeutic effectiveness.
Keywords: Eosinophil cationic protein, atopic bronchial asthma, gastroesophageal reflux disease, systemic inflammation, IgE, eosinophil activation, biomarkers.